Viral proteins recognized by different TLRs. Issue 11 (17th August 2021) - Zhou, Rui; Liu, Li; Wang, Yu
Abstract: Virus invasion activates the host's innate immune response, inducing the production of numerous cytokines and interferons to eliminate pathogens. Except for viral DNA/RNA, viral proteins are also targets of pattern recognition receptors. Membrane‐bound receptors such as Toll‐like receptor (TLR)1, TLR2, TLR4, TLR6, and TLR10 relate to the recognition of viral proteins. Distinct TLRs perform both protective and detrimental roles for a specific virus. Here, we review viral proteins serving as pathogen‐associated molecular patterns and their corresponding TLRs. These viruses are all enveloped, including respiratory syncytial virus, hepatitis C virus, measles virus, herpesvirus human immunodeficiency virus, and coronavirus, and can encode proteins to activate innate immunity in a TLR‐dependent way. The TLR‐viral protein relationship plays an important role in innate immunity activation. A detailed understanding of their pathways contributes to a novel direction for vaccine development. Abstract : Highlights: 1. The TLR‐viral protein relationship plays an important role in innate immunity activation 2. we review viral proteins serving as pathogen‐associated molecular patterns and their corresponding TLRs. 3. Respiratory syncytial virus, hepatitis C virus, measles virus, herpesvirus human immunodeficiency virus, and coronavirus, and can encode proteins to activate innate immunity in a TLR‐dependent way.